2021
DOI: 10.1177/10668969211041592
|View full text |Cite
|
Sign up to set email alerts
|

Renal Oncocytoma With Both Lymphovascular Invasion and Prominent Intracytoplasmic Vacuole-Like Spaces: A Case Report and Review of the Literature

Abstract: Here we report a case of renal oncocytoma in a 68 year-old male. The diagnosis was initially made on a needle biopsy 6 years prior to the partial nephrectomy. The case is unique that in addition to the gross and microscopic features commonly seen in renal oncocytomas, both lymphovascular invasion and prominent intracytoplasmic vacuole-like spaces are also present in this tumor. Although vascular invasion is increasingly recognized as compatible with renal oncocytoma, intracytoplasmic vacuoles are a rare and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…CgA and syn have high specificity and NSE sensitivity. Some scholars have found that CGA is related to tumor development and prognosis, so it can be used as a marker to detect tumor recurrence and evaluate prognosis [16,17]. GST has a potential malignant tendency.…”
Section: Ct Image Detection G-nec Imagementioning
confidence: 99%
“…CgA and syn have high specificity and NSE sensitivity. Some scholars have found that CGA is related to tumor development and prognosis, so it can be used as a marker to detect tumor recurrence and evaluate prognosis [16,17]. GST has a potential malignant tendency.…”
Section: Ct Image Detection G-nec Imagementioning
confidence: 99%
“…Luo et al reported a case of oncocytoma displaying lymphovascular invasion with concomitant prominent intracytoplasmic vacuole-like spaces, which is seldom documented in the literature but does not preclude a proper oncocytoma diagnosis if the cytological, architectural and IHC findings are suggestive of oncocytoma, and its mimics have been excluded, particularly succinate–dehydrogenase-deficient renal cell cancer [ 110 ].…”
Section: Macroscopic and Microscopic Appearancementioning
confidence: 99%